1985
DOI: 10.1007/bf00005152
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative field investigations of feeding and territorial behaviour of young-of-the-year brook charr, Salvelinus fontinalis

Abstract: SynopsisDirect observations of young-of-the-year brook charr, Salvelinus fontinalis, in a second-order woodland stream indicated that most of their feeding effort was directed toward sub-surface, drifting prey (83% of feeding time) . Feeding from the substrate and water surface was much less frequent (17% of feeding time) . Comparisons of gut contents to drift net and substrate fauna samples corroborated that the most commonly consumed prey (chironomid and trichopteran larvae, ostracods, and ephemeropteran nym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…Aggression between fish was greatest when the subordinate fish temporarily moved into an upstream position relative to the dominant. Similar observations have been previously reported for a number of different salmonids (McNicol & Noakes 1981, McNicol et al 1985, Grant et al 1989). For example, Grant et al (1989) found that defense effort by brook charr was significantly greater in an upstream rather than downstream direction.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Aggression between fish was greatest when the subordinate fish temporarily moved into an upstream position relative to the dominant. Similar observations have been previously reported for a number of different salmonids (McNicol & Noakes 1981, McNicol et al 1985, Grant et al 1989). For example, Grant et al (1989) found that defense effort by brook charr was significantly greater in an upstream rather than downstream direction.…”
Section: Discussionsupporting
confidence: 85%
“…However, in all his experiments, Fausch reported that individual fish moved and temporarily took up position in other 'atypical positions'. Such movement from typical, or preferred, feeding sites to other locations in the stream by salmonids has also been reported in a number of other studies (Jenkins 1969, Wankowski & Thorpe 1979, Bachman 1984, McNicol et al 1985. We feel this movement among sites may represent sampling of available foraging sites by individual fish.…”
Section: Introductionmentioning
confidence: 59%
“…The YOY in both habitats had achieved a size of ~40 mm and lg by July. Such growth is comparable with fluvial (McNicol et al 1985, Randall 1982 and lacustrine (Griswold 1967) stocks. The apparent quantity of food was similar between the lake and creek habitats in Meach Lake, but differences in food types and possibly energetic values existed.…”
Section: Discussionmentioning
confidence: 65%
“…The ecology of stream-dwelling brook charr, Salvelinus fontinalis, during their first weeks of exogenous feeding have been described (e.g., McNicol et al 1985, Williams 1981. Although lake-dwelling populations of brook charr are common, the ecology of their early life history stages is not as well known.…”
Section: Introductionmentioning
confidence: 99%
“…The fauna, in turn, constitute an important part of the diet of many freshwater fishes (Williams 1981;McNicol et al 1985;Brown et al 1989;Schmid-Araya & Schmid 2000;Ranga Reddy 2001) and predaceous invertebrates (Benke & Wallace 1980;Schmith & Smock 1992;SchmidAraya & Schmid 2000). The usefulness of hyporheic fauna as indicators (biosensors) of anthropogenic impacts such as pollution has also been documented for certain groups (Notenboom et al 1994;Boulton 2000a,b).…”
Section: Introductionmentioning
confidence: 99%